Seasonality of births in horizontal strabismus: comparison with birth seasonality in schizophrenia and other disease conditions. (22nd December 2019) - Agarwal, A. B.; Cassinelli, K.; Johnson, L. A.; Matsuda, K.; Kirkpatrick, B.; Yang, W.; von Bartheld, C. S.
Abstract: Recent work has implicated one type of horizontal strabismus (exotropia) as a risk factor for schizophrenia. This new insight raises questions about a potential common developmental origin of the two diseases. Seasonality of births is well established for schizophrenia. Seasonal factors such as light exposure affect eye growth and can cause vision abnormalities, but little is known about seasonality of births in strabismus. We examined birth seasonality in people with horizontal strabismus in a retrospective study in Washoe County, Nevada, and re-examined similar previously obtained data from Osaka, Japan. We then compared seasonal patterns of births between strabismus, refractive error, schizophrenia and congenital toxoplasmosis. Patients with esotropia had a significant seasonality of births, with a deficit in March, then increasing to an excess in September, while patients with exotropia had a distinctly different pattern, with an excess of births in July, gradually decreasing to a deficit in November. These seasonalities were statistically significant with either χ 2 or Kolmogorov–Smirnov-type statistics. The birth seasonality of esotropia resembled that for hyperopia, with an increase in amplitude, while the seasonality for myopia involved a phase-shift. There was no correlation between seasonality of births between strabismus and congenital toxoplasmosis. The pattern of an excess of summer births for people with exotropia was remarkably similar to the well-established birth seasonality of one schizophrenia subtype, the deficit syndrome, but not schizophrenia as a whole. This suggests a testable hypothesis: that exotropia may be a risk factor primarily for the deficit type of schizophrenia.